The implications of the rights-based approach on NGOs' funding. Issue 4 (19th May 2017) - Olawoore, Babatunde
ABSTRACT: Existing literature suggests that NGOs that adopt the rights-based approach (RBA) may secure more funds from rights-based donors, otherwise they would face funding cuts from such donors. This article investigates the extent to which RBA affects decisions made by ActionAid, intermediate NGOs, and CBOs on accepting certain funding conditions. Research participants from NGOs stated that RBA limits their funding because many donors prefer service delivery. They are also selective about where they apply for funds. For CBO participants, RBA posed fewer problems in terms of their funding decisions. Intermediate NGO and CBO participants claimed that RBA motivates them to locate alternative funding sources locally.